Leadership Strategies in Improving Higher Education Graduates' Competitiveness - Hatmansyah Hatmansyah; Iim Wasliman; Husen Saeful Insan; Hanafiah Hanafiah (Universitas Bengkulu, 2021)
Strong, visionary, and effective leadership are the main pillars in developing and improving competitiveness of educational institution. This research focused on the leadership strategies in improving higher education graduates’ competitiveness in Faculty of Education and Teacher Training of UIN Antasari Banjarmasin and Polytechnic of Hasnur Banjarmasin. This research employed a descriptive qualitative approach with a case study method to obtain an overview about the implementation of millennial leadership characters to improve the Higher Education competitiveness: 1) strategies for building sustainable competitiveness excellence; 2) implementing strategies through Leadership and Culture; 3) Strategies for sustainable supervision and improvement; 4) strategic steps to overcome problems and weaknesses; 5) creative and innovative ideas in increasing Higher Education graduates’ competitiveness. Finally, this research found out that leadership strategy in improving University graduates’ competitiveness had been implemented based on the national Higher Education standards and the stipulation of the Educational Quality Assurance Council. Nevertheless, supervision strategies had not demonstrated maximum efforts, especially in the development and improvement of graduates’ quality and competitiveness.